Real effects of an international tax reform for MNEs - Regina Ortmann; Dirk Simons; Dennis Voeller (Arbeitskreis Quantitative Steuerlehre (arqus), 2021)
With multinational enterprises (MNEs) centralizing production facilities, market countries claim not to receive their fair share of taxes. A reform of international business taxation that includes new profit allocation rules as well as the introduction of minimum taxation is being considered as a problem mitigating mechanism. We analyze theoretically the real effects of the aforementioned tax reform, i.e., MNEs' adjustments of production and sales decisions. Our findings show that the effects of an international tax reform on sales quantities depend on the properties of the underlying product markets. If national demand resembles characteristics of traditional industries, sales quantities remain unchanged. However, sales quantities are affected if specific demand characteristics of modern business models are assumed. For traditional industries a reformed tax regime increases tax revenues in high-tax market countries and even attracts production. In contrast, for modern business models tax revenues of high-tax countries can even decrease.
Keywords: C70; H26; H32; M48; 330; BEPS; corporate taxation; minimum taxation; profit shifting; tax avoidance